P0110 Safety and anti-tumour activity of pegylated recombinant human IL-10 (AM0010) in selected advanced solid tumours. (July 2015) - Naing, A; Infante, J.R.; Papadopoulos, K.P.; Autio, K.A.; Ott, P.A.; Falchook, G.; Wong, D.; Whiteside, M.; Oft, M.
Abstract : Background: Cancer immunotherapy targets the activation of tumour infiltrating CD8 T cells. IL-10 directly stimulates the cytotoxic activity of CD8 T cells and immunoglobulin production of B cells and it has anti-inflammatory activity. In mice, pegylated IL-10 (AM0010) but not non-pegylated-IL-10 induces the rejection of tumours and the development of immunological memory against the tumour cells. A first-in-human study with AM0010 was started in November, 2013. The primary objectives were to establish the safety, tolerability, and the maximum tolerated dose of AM0010. Secondary objectives are to assess preliminary anti-tumour activity, pharmacokinetics, and immunogenicity of AM0010 in monotherapy and in combination with chemotherapy. Methods: This ongoing phase 1 study explores monotherapy and combinations with several approved cancer therapies. At this point, 98 patients with advanced solid tumours were enrolled. Patients self-administrate subcutaneous doses of AM0010. Up to six patients with advanced solid tumours were enrolled per cohort in the escalation phase, followed by disease specific expansion cohorts of 10–15 patients. Patients with melanoma, non-small-cell lung cancer, renal cell cancer, colorectal cancer, castrate-resistant prostate cancer, ovarian cancer, and pancreatic cancer were enrolled during the monotherapy dose escalation phase. Additional indications were explored in combination therapies. Findings: AM0010 was well tolerated as monotherapy and in combination with two chemotherapy regimens. An active dose has been established in monotherapy, but the maximum tolerated dose has not yet been established. Early signs of clinical activity were observed, including partial responses in monotherapy and in combination with chemotherapy. Reductions in tumour markers were observed in a variety of tumour types with radiological or metabolic responses observed in renal cell carcinoma, gastroesophageal cancer, breast cancer, and anal cancer. Correlates of systemic immune activation and intra-tumoral activation of CD8 T cells were noted. Interpretation: AM0010 provides a unique immune stimulation with clinical activity in a variety of oncology indications.